Improving hydrogen production for carbon-nitride-based materials: crystallinity, cyanimide groups and alkali metals in solution working synergistically. Issue 35 (22nd August 2022) - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Atta Diab, Gabriel Ali; Salas, Nieves López; Savateev, Aleksandr; Antonietti, Markus
Abstract : The recent findings on the fundamental understanding of the activity of carbon nitride-based materials in the hydrogen evolution reaction (HER) allow to design rationally the photocatalytic systems with improved activities. Abstract : The recent findings on the fundamental understanding of the activity of carbon nitride-based materials in the hydrogen evolution reaction (HER) allow to design rationally the photocatalytic systems with improved activities. Herein, combining highly ordered materials with cyanimide defects and alkali metal cations in the solution, we demonstrated an important synergistic effect which for cyanimide modified K-PHI is revealed in 12 times higher apparent quantum yield (AQY) compared to K-PHI free of surface cyanimide groups.